2010
DOI: 10.1017/s1047951109991132
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy-proven myocardial sequels in Kawasaki disease with giant coronary aneurysms

Abstract: Whether the abnormalities were due to direct myocardial injury, chronic ischaemia, repeated small-vessel thrombosis, or other problems associated only with biopsies, is difficult to determine. However, this subgroup had residual abnormal lesions in the myocardium. Follow-up should be more aggressive in this group of patients to identify myocardial damage that could be asymptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…[294][295][296] In a more recent study of 16 patients with giant aneurysms, initial biopsy samples showed myocyte degeneration, hypertrophy, and inflammatory cell infiltration, whereas follow-up biopsy specimens showed myocyte disarray, interstitial fibrosis, and ongoing inflammatory cell infiltration. 297 The pathogenesis of the abnormalities was not clear, but the sites of the aneurysms were not related to the biopsy findings. Subsequent studies of myocardial characterization and function have reported variable findings.…”
Section: Myocardial Abnormalitiesmentioning
confidence: 99%
“…[294][295][296] In a more recent study of 16 patients with giant aneurysms, initial biopsy samples showed myocyte degeneration, hypertrophy, and inflammatory cell infiltration, whereas follow-up biopsy specimens showed myocyte disarray, interstitial fibrosis, and ongoing inflammatory cell infiltration. 297 The pathogenesis of the abnormalities was not clear, but the sites of the aneurysms were not related to the biopsy findings. Subsequent studies of myocardial characterization and function have reported variable findings.…”
Section: Myocardial Abnormalitiesmentioning
confidence: 99%
“…reported myocardial changes including hypertrophy, degeneration of myocytes, and interstitial fibrosis in the majority of biopsies obtained at least 3 years after, at various time points after the acute illness and their presence was more frequent in patients who had suffered coronary artery aneurysms during the acute phase. [19] Yutani et al . had previously found myocardial abnormalities including lymphocyte and plasma cell infiltration, myocardial fibrosis, and disarray of myocardial fibers in Kawasaki disease convalescent patients.…”
Section: Discussionmentioning
confidence: 99%
“…In general, myocardial fibrosis is related to either replacement fibrosis after myocardial infarction or interstitial fibrosis as a sequela of myocardial inflammation, which is universally present during acute KD according to endomyocardial biopsy studies from Japan [4, 5, 28]. A systematic study of 29 KD patients who died within the first 40 days after fever onset demonstrated myocarditis with varying degrees of infiltration of inflammatory cells in all cases [29].…”
Section: Discussionmentioning
confidence: 99%